Validation of an integrated control system with improvement in efficiency and reliability of the decisions made for monitoring - Bekirova, Lala Rustam (Eastern-European Journal of Enterprise Technologies, 2017)
A technique is proposed to improve reliability of data from the remote RGB measurements in order to shorten the time needed for determining local leakages in the main pipelines during monitoring. To improve spatial resolution and geometrical accuracy in the RGB measurements, it is proposed to use the IR and panchromatic measurements in combination, using controlled liquid crystal filters. In this case, visualizing the IR data (employing conditional colors) and comparing them with the data of actual colors in the RGB measurements is used to improve accuracy of data from the remote measurements. We also developed a technique for the remote and locally synchronous ground-based measurements to validate and correct their results with a certain error, which allows rapid assessment of the condition of examined area based on data from the remote measurements taking into account a validation by possible ground-based measurements. In this case, the designed structure of an automated system simultaneously monitors main production processes and assesses ecological condition of the corresponding sites, thus addressing the set task in a comprehensive manner. The results obtained improve efficiency of determining local leakages and the boundaries of plots, polluted in varying degree as a consequence of manufacturing processes, and facilitate making a correct decision while monitoring the environment